Ethanol extract of Brazilian propolis ameliorates cognitive dysfunction and suppressed protein aggregations caused by hyperhomocysteinemia. Issue 11 (2nd November 2015) - Miyazaki, Yuta; Sugimoto, Yasushi; Fujita, Akikazu; Kanouchi, Hiroaki
Abstract: Homocysteine (Hcy) has been proposed to be a risk factor for cognitive dysfunction. We investigated the effects and the underlying mechanisms of action of propolis, which has antioxidant activity on Hcy-induced oxidative stress in vitro and in vivo . For the in vitro assays, neuroblastoma SH-SY5Y and glioblastoma U-251MG cells were cultured with Hcy and various concentrations of propolis. Cell death and reactive oxygen species production were significantly suppressed by propolis in dose-dependent manner, compared with Hcy alone. For the in vivo assays, mice were fed a propolis-containing diet and Hcy thiolactone in water. Cognitive function was evaluated using the Morris water maze test. Propolis suppressed cognitive dysfunction caused by hyperhomocysteinemia. Accumulation of aggregated protein in brain was accelerated in hyperhomocysteinemia, and the accumulation was suppressed by propolis. Hyperhomocysteinemia, however, did not enhance the oxidative stress in brain. In vitro amyloid formation assay showed that Hcy accelerated lysozyme aggregation and propolis inhibited the aggregation. Graphic Abstract: : Oral feeding of homocysteine thiolactone caused the cognitive dysfunction in mice. Brazilian Propolis ameliorated the cognitive dysfunction and suppressed the protein aggregation in hippocampus.